Niveles de comprensión lectora en estudiantes del quinto grado de primaria de la Institución Educativa El Zeario Mac Donald, Pebas 2021 - Flores Butuna, Mayquer Freddy (2022)
The objective of this research was to determine the levels of reading comprehension presented by the students of the fifth grade of primary education of the Educational Institution El Zeario Mac Donald, Pebas- 2021. Being the type of explanatory study with a non-experimental, cross-sectional design. The study population consisted of 39 students in the fifth grade of primary school and the sample unit was the same, applying the census method for convenience. The data was collected through a written test of reading comprehension, the instruments were validated by expert judgment in advance. The results show that the variable levels of reading comprehension, the students have better comprehension in the literal level, 41.0% marked correct, while 10.3% failed. At the inferential level, problems are observed in the interpretation and deduction of the information, for which the following results were obtained: 10.3% marked correctly, while 15.4% failed. At the critical level, it is observed that they have a knowledge of reality to be able to interpret and comment on the context of their social environment and biodiversity, 12.8% answered correctly and 10.3% failed in the answers. It is necessary to specify that the literal level is the one that had the highest percentage of correct answers, while the inferential level and the critical level have more failures than successes in fifth grade students of the Zeario Mac Donald educational institution, Pebas 2021.